Cassava Virus Diseases and their control - Africa Agriculture Science Week (AASW6) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Eugene R. Terry from TransFarm Africa says that the African Agriculture Science Week is a very important event, which gives an opportunity to talk about control measures for African cassava virus diseases and their control. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/... http://www.fara-africa.org/scienceweek/